2012
DOI: 10.1063/1.4739245
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cross-hatched polariton disorder in GaAs/AlAs microcavities by strain compensation

Abstract: An angle modulation reflectance spectroscopy characterization of a GaAs/GaAlAs asymmetric microcavity structure Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Although elastic scattering due to disorder has been previously observed for organic polaritons in the linear regime [25], the local intensity fluctuations seen here only appear beyond the condensation threshold. These bear striking similarities to those observed in disordered inorganic microcavities [16,23,26,27].Although a number of other criteria exist, the spontaneous onset of long-range spatial coherence is often recognized as a defining feature for condensation. This was first reported for a CdTe microcavity in the seminal work of Kasprzak et al using a Michelson interferometer with one arm replaced by a retroreflector [27].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Although elastic scattering due to disorder has been previously observed for organic polaritons in the linear regime [25], the local intensity fluctuations seen here only appear beyond the condensation threshold. These bear striking similarities to those observed in disordered inorganic microcavities [16,23,26,27].Although a number of other criteria exist, the spontaneous onset of long-range spatial coherence is often recognized as a defining feature for condensation. This was first reported for a CdTe microcavity in the seminal work of Kasprzak et al using a Michelson interferometer with one arm replaced by a retroreflector [27].…”
mentioning
confidence: 65%
“…Organics offer the advantage of a broad spectral range beyond that covered by GaN and ZnO and can be easily fabricated without the need for epitaxial growth. As-grown films, however, tend to be highly disordered and to overcome possible localization effects [12][13][14][15][16][17][18][19][20][21][22][23][24], the first demonstration of organic polariton condensation used a single-crystalline organic semiconductor as the active material [1]. Two recent demonstrations, however, have shown that the same phenomenology can be extended to amorphous systems: one consisting of a spin-coated polymer [3] and the other of a thermally evaporated oligomer [2].…”
mentioning
confidence: 99%
“…It was shown by Zajac, Langbein, and Clarke that even an empty cavity with a similar number of DBR repeats may undergo strain relaxation. 12 In sample 2, the number of DBR repeats and QWs, and thus total strain is reduced, which is reflected in the reduced level of crosshatching.…”
mentioning
confidence: 99%
“…Several schemes have been proposed to compensate for this lattice mismatch, through the use of pseudo-alloys 11 or by incorporation of strain compensating layers of AlP in the DBR layers. 12 However, the growth of high-quality and homogeneous microcavities remains a technical obstacle to fundamental research and to the development of polaritonic devices.…”
mentioning
confidence: 99%
“…Nevertheless, the presence of cross-hatched dislocations affects the dynamics of polaritons giving rise to localization 14 and scattering [15][16][17][18] phenomena that limit the propagation of polaritons within the cavity plane. In our previous work, 19 we have shown that one can reduce the cross-hatched dislocation density by introducing strain-compensating AlP layers into the centre of the AlAs layer of the distributed Bragg reflectors (DBRs). Here, we report on polariton condensation in a planar, strain compensated 2k GaAs microcavity with embedded InGaAs QWs under non-resonant optical excitation.…”
mentioning
confidence: 99%